Introduction to epigenetics - Ruddy, Suzanne (Henry Stewart Talks, 2020)
Definition of epigenetics, Three mechanisms; DNA methylation, histone modification, ncRNA, Hypo and hyper DNA methylation and association with transcriptional state, Mechanism of DNA methylation and enzymes responsible, Examples of importance of DNA methytransferase enzymes, Main types of histone modifications, concentrating on acetylation and methylation, Mechanisms and enzymes for histone modifications, Example of gene regulation by acetylation/deacetylation in Arabidopsis, Non-coding RNA, using X-inactivation as an example, The histone code